The relationship between employee empowerment, team work and recognition on company performance: An investigation in Malaysian manufacturing industry - Chua, G. S.; Jusoh, Muhammad Shahar; Amlus, Mohamad Harith; Abidin, Rahimi; Ibrahim, Amlus (INSInet Publications, 2014)
In current globalization business competition scenario, every organization or company is striving to maximize it earning profits. This study attempts to explore the relationship between employee empowerment, team work and recognition which could potentially influence company performance. Company Performance is the main criteria for a company continue to growth, gain market place, success and survival in near future more or less affecting by the employee involvement and emotional commitment to the company.Through a survey, a total 84 companies representing various industries in Northern Region of Malaysia had responded. The hypotheses involved were tested using correlation and regression techniques. The results of the study support all the hypotheses.The multiple regression analysis indicates that there are significant relationships among the factors on each criterion to manufacturing capabilities.